Inflationary Universe from Anomaly-Free FR-Gravity - Aroonkumar Beesham; Kazuharu Bamba (Advances in High Energy Physics)
By adding a three-dimensional manifold to an eleven-dimensional manifold in supergravity, we obtain the action of FR-gravity and find that it is anomaly-free. We calculate the scale factor of the inflationary universe in this model and observe that it is related to the slow-roll parameters. The tensor-scalar ratio Rtensor−scalar is in good agreement with experimental data.